PENGARUH TIPE KEPRIBADIAN TERHADAP HASIL BELAJAR MATEMATIKA DENGAN INTERVENSI METODE TIME QUIZ - Faza Miftakhul Farid; Yunni Arnidha; Yesi Budiarti (JANACITTA, 2021)
Personality type is a trait that every student has. Personality type will affect the learning outcomes of mathematics after intervention with themethod time quiz. This study entitled "The Influence of Students' Personality Types on Mathematics Learning Outcomes WithMethod Intervention Time Quiz" with the formulation of the problem whether the differences and comparisons of student learning outcomes based on students' personality types. This study aims to determine the differences and comparisons of student learning outcomes based on students' personality types.The research method used is a quantitative method with aresearch quasi-design experimentaltype One-Shot case study. The sample in this study was class V SD Muhammadiyah Ambarawa, totaling 24 students with a sampling technique, namely the saturated sample technique.Based on the results of the t-test analysis (Paired Sample T-Test), it is obtained that the t-countÂ  is smaller than the t-table, namely 0.283 <1.782. So it can be concluded that there is no difference in the mathematics learning outcomes of studentspersonality extrovert withand the mathematics learning outcomes of students withpersonalities introverted who are given themethod time quiz. In this study also resulted that students who have anpersonality extroverted are higher with an average value of 6.50. The average value is greater thanberpekribadian students introvet with an average score of 6.33.